2016
DOI: 10.3758/s13414-016-1105-8
|View full text |Cite
|
Sign up to set email alerts
|

Visual working memory simultaneously guides facilitation and inhibition during visual search

Abstract: During visual search, visual working memory (VWM) supports the guidance of attention in two ways: It stores the identity of the search target, facilitating the selection of matching stimuli in the search array, and it maintains a record of the distractors processed during search so that they can be inhibited. In two experiments, we investigated whether the full contents of VWM can be used to support both of these abilities simultaneously. In Experiment 1, participants completed a preview search task in which (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…This is not to say that advance suppression cannot occur. First, there is ample behavioral and neuroscientific evidence for the anticipatory suppression of perceptual processing at an expected distractor location (Dube, Basciano, Emrich, & Al-Aidroos, 2016;Al-Aidroos, Emrich, Ferber, & Pratt, 2012;Händel et al, 2011;Munneke, Van der Stigchel, & Theeuwes, 2008;Rihs et al, 2007;Ruff & Driver, 2006;Serences, Yantis, Culberson, & Awh, 2004), but this does not demonstrate the feature-based, distractorspecific advance inhibition that we were after here. A previous report that claimed such advance feature-based inhibition (Arita et al, 2012) may have contaminated the to-be-ignored feature with a consistent spatial location (Beck & Hollingworth, 2015;Becker et al, 2015).…”
Section: No Evidence For An Advance Inhibitory Templatementioning
confidence: 57%
“…This is not to say that advance suppression cannot occur. First, there is ample behavioral and neuroscientific evidence for the anticipatory suppression of perceptual processing at an expected distractor location (Dube, Basciano, Emrich, & Al-Aidroos, 2016;Al-Aidroos, Emrich, Ferber, & Pratt, 2012;Händel et al, 2011;Munneke, Van der Stigchel, & Theeuwes, 2008;Rihs et al, 2007;Ruff & Driver, 2006;Serences, Yantis, Culberson, & Awh, 2004), but this does not demonstrate the feature-based, distractorspecific advance inhibition that we were after here. A previous report that claimed such advance feature-based inhibition (Arita et al, 2012) may have contaminated the to-be-ignored feature with a consistent spatial location (Beck & Hollingworth, 2015;Becker et al, 2015).…”
Section: No Evidence For An Advance Inhibitory Templatementioning
confidence: 57%
“…Again, this work could be interpreted as suggesting that participants were able to use the preview frame to prepare to suppress processing of the featured distractors. Indeed, when the number of preview items is below working memory capacity there appears to be little impact of the presence of a distractor [51]. However, according to the predictive coding framework outlined above, processing the distractor stimuli prior to the target presentation removes the need for further processing during the search task.…”
Section: Behavioural Evidence For Preparatory Distractor Inhibitionmentioning
confidence: 99%
“…Whereas Olivers et al suggested that only one item in WM can be in the active status at a time, a recent study demonstrated that visual search can be biased by multiple items in WM, not just the active item (Hollingworth & Beck, 2016). Another study also challenged the one-active-item idea by showing that while one item in memory serves as the target template leading to attentional capture, other items in memory may guide the inhibition of distractors (i.e., Dube et al, 2016). However, the present findings are consistent with Olivers et al’s idea, by suggesting that the memorised items from the memory task are in the accessory status and cannot affect the stimulus processing time of visual search.…”
Section: Discussionmentioning
confidence: 99%
“…This visual working memory (VWM) load account may well explain the increase in overall RT when WM is occupied, but its basic assumption requires more empirical testing. To our knowledge, no study has ever shown a turning point near set size four in the RT × set size function in standard visual search (i.e., with items in the search array being presented all at once), although a turning point in the search efficiency at search set sizes close to the WM capacity has been reported by the preview search paradigm, in which part of the search items are previewed before all items are shown (Al-Aidroos, Emrich, Ferber, & Pratt, 2012; Dube, Basciano, Emrich, Al-Aidroos, 2016).…”
Section: Introductionmentioning
confidence: 99%